2019
DOI: 10.1017/s0033291719001855
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions using virtual reality for pain associated with medical procedures: a systematic review and meta-analysis

Abstract: BackgroundVirtual reality (VR) may enhance the effectiveness of psychological interventions for acute pain. We conducted a meta-analysis to assess the efficacy and safety of VR-based interventions for pain associated with medical procedures.MethodsWe searched PubMed, EMBASE, the Cochrane Library, and PsycINFO until June 17th 2018. We identified randomized controlled trials (RCTs), comparing VR-based psychological interventions to usual care, for pain intensity (primary outcome) or affective and cognitive compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 76 publications
3
33
0
Order By: Relevance
“…For example, VR interventions have been applied in rehabilitation (Laver et al, 2017), habilitation (Snider et al, 2010), psychiatry (Freeman et al, 2017), geriatrics (Neri et al, 2017), and palliative care (Niki et al, 2019). An increasing number of studies have demonstrated its utility in the management of pain and anxiety caused by medical procedures in adult and pediatric populations (Malloy and Milling, 2010;Chan et al, 2018;Eijlers et al, 2019b;Georgescu et al, 2020).…”
Section: Virtual Reality In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…For example, VR interventions have been applied in rehabilitation (Laver et al, 2017), habilitation (Snider et al, 2010), psychiatry (Freeman et al, 2017), geriatrics (Neri et al, 2017), and palliative care (Niki et al, 2019). An increasing number of studies have demonstrated its utility in the management of pain and anxiety caused by medical procedures in adult and pediatric populations (Malloy and Milling, 2010;Chan et al, 2018;Eijlers et al, 2019b;Georgescu et al, 2020).…”
Section: Virtual Reality In Healthcarementioning
confidence: 99%
“…Previous reviews have indicated the potential of VR in pediatrics (e.g., Indovina et al, 2018;Eijlers et al, 2019a;Georgescu et al, 2020;Lambert et al, 2020). Its immersive, interactive nature is thought to provide particularly captivating distraction, as well as a cost-effective and engaging medium for procedural preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Using G*Power 3.1.9.2 (39), we had estimated a minimum of 50 participants (25 in each group) needed to detect an effect size of 0.49, with α = 0.05 and power =0.80. The expected effect size of 0.49 was chosen in the light of the results found by the most recent meta-analyses (25,26), being a conservative effect size given that in their analysis Chan and colleagues (25) found a medium effect size (SMD= -0.49, 95% CI -0.83 to -0.14) and the analysis of Georgescu and colleagues (26) a large effect size was found (Hedges'g =1.08, 95% CI 0.46 to 1.70) for studies with parallel design aiming to decrease pain at hospitalized patients. However, as we expected some dropouts (based on other studies using VR systems for treating anxiety (40)) and some incomplete or unusable data, especially on the physiological measure, we aim to recruit 30 participants in each group.…”
Section: Study Sample Sizementioning
confidence: 99%
“…A recent metaanalysis (25) estimating the e cacy of VR interventions for acute pain management in clinical settings found a medium effect size of these interventions (standard mean differences (SMD) = -0.49, 95% CI -0.83 to -0.14). Moreover, a subsequent meta-analysis (26) relying only on randomized controlled trials (RCT) conducted in hospital settings, showed signi cant effects of VR-based interventions to reduce pain intensity during medical procedures (7 studies, Hedges'g = 1.09, 95% CI 0.25 to 1.92) and after the medical procedures (12 studies, Hedges'g = 1.08, 95% CI 0.46 to 1.70). Moreover, comparable results were founded when interventions aimed to reduce the cognitive (8 studies, Hedges'g = 0.82, 95% CI 0.39 to 1.26) or affective components of pain (14 studies, Hedges'g = 0.55, 95% CI 0.34 to 0.77).…”
Section: Introductionmentioning
confidence: 99%
“…Using G*Power 3.1.9.2 (39), we had estimated a minimum of 50 participants (25 in each group) needed to detect an effect size of 0.49, with α = 0.05 and power =0.80. The expected effect size of 0.49 was chosen in the light of the results found by the most recent meta-analyses (25,26), being a conservative effect size given that in their analysis Chan and colleagues (25) found a medium effect size (SMD= -0.49, 95% CI -0.83 to -0.14) and the analysis of Georgescu and colleagues (26) a large effect size was found (Hedges'g =1.08, 95% CI 0.46 to 1.70) for studies with parallel design aiming to decrease pain at hospitalized patients. Moreover, as we expected some dropouts (based on other studies using VR systems for treating anxiety(40)) and some incomplete or unusable data, especially on the physiological measure, we aimed to recruit 30 participants in each group.…”
Section: Study Sample Sizementioning
confidence: 99%